Corrosion behavior of Ti/Al laminate composites as electrode of chlor-alkali electrolysis. (28th April 2020) - Wang, Lixia; Sun, Limin; Cao, Yang; Shen, Jing
High-performance electrodes can solve problems of high voltage and large electricity consumption existing in chlor-alkali industry. A Ti/Al laminate composite (named as Ti/Al-LC) with three-layered structure (Ti/Al3 Ti/Ti) is prepared as a new type of anode electrode for chlor-alkali electrolysis. Scanning electron microscope observation shows that the Ti/Al-LC is composited of a thicker inner layer with thickness about 700 µm and two thinner outer layers with thickness about 300 µm. From the X-ray diffraction pattern, it is known that the outer layers consisted of α-Ti and β-Ti phases, while the inner layer consisted of Al3 Ti intermetallic phase. A saturated sodium chloride (NaCl) solution at 70°C is purposely chosen as the corrosion electrolyte to analyze the corrosion behavior of Ti/Al-LC as anode electrode for chlor-alkali electrolysis. Electrochemical tests, including potentiodynamic polarization and electrochemical impedance spectroscopy measurements, on a three-electrode system indicate that the Ti/Al-LC has a low corrosion rate with corrosion current density of 1.94 µA cm −2 and stable surface passive film in saturated NaCl solution at 70°C.